ASUHAN KEBIDANAN PADA IBU NIFAS DENGAN PERAWATAN LUKA PERINEUM DI UPT PUSKESMAS TANJUNG BALAI - Puti Lenggo Geni; Risqi Utami (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
Postpartum period is a very important period because at that time it was very proneto complications including postpartum infection. One of the factors causing childbirthinfection can come from birth canal injury which is a good medium for developing germs.emergence of infection in the perineum can spread to the bladder or in birth canalwhich can result in complications of the birth canal infection so that treatment ofperineal wounds is needed. Perineal rupture occurs almost in all first labor and is not uncommon insubsequent labor. e perineal rupture generally occurs in the midline and may become widespread ifthe fetal head is born too soon, the pubic arch angle is smaller than usual, the fetal head passes through the pelvic door that is larger in size than the subregional subreglysia of bregmatika. Perineal wound is injury to the urogenital diaphragm and the leucator ani muscle, which occurs during normal labor, or labor with the device, can occur without injury to the skin of the perineum or to thevagina, so that it is not visible from the outside.This study aims to determine whether perineal wound care can accelerate perineal wound healing. This research study using the case study method conducted at Tanjung Balai Karimun Health Center in January until February 2023. data collection method is participatory observation, interviews, measurements, documentation. Research results show that good and correct perineal wound care can help speed up the healing of perineal wounds in Mrs “M” at the TgBalaiKarimun Health Center in 2023.